Ausbreitung der Pflanze Telekia speciosa und der Blattlaus Uroleucon telekiae (Holm.) (Homoptera: Aphididae). - Müller, Fritz Paul; Steiner, Hanna (Contributions to Entomology = Beiträge zur Entomologie, 1989)
Uroleucon telekiae (Holman, 1965) described from eastern Slovakia was found near Rostock and for the first time in the territory of the GDR. Its host plant, Telekia speciosa (Schreber) Baumgart., which originates from southeastern Europe, Asia Minor and Transcaucasia, was first introduced as an ornamental plant. Later on it grew wild, and now it occurs in many places in dense stands mainly on rims and glades of forests. All five morphs of the aphid are described.